New Roles for Academic Libraries in Scientific Information - Bertnes, Pål A. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
In this presentation I will focus on the situation and development of academic libraries both in a macro and micro perspective. The macro perspective comprises society as a whole, higher education and research – areas in which libraries believe they have little or no influence. The micro perspective comprises conditions within the libraries or within the political and economic framework of the libraries.